The role of multiple attachments in intergenerational transmission of child sexual abuse among male victims. (June 2022) - Miljkovitch, Raphaële; Danner-Touati, Camille; Gery, Isabelle; Bernier, Annie; Sirparanta, Aino; Deborde, Anne-Sophie
Highlights: Intergenerational transmission of child sexual abuse is associated with pervasive disorganized attachment representations. The link between attachment to father and intergenerational transmission of child sexual abuse is mediated by attachment to romantic partner. Attachment to romantic partner moderates the risk of abusing children associated with insecure and disorganized attachment to mother among male child sexual abuse victims. Abstract: Background: According to Finkelhor (1984), difficulties child sexual abusers have in establishing adaptive adult relationships are a consequence of attachment problems with parents. Research shows that insecure attachment is associated with both the experience of child sexual abuse (CSA) as a victim and perpetration of CSA as an adult. Attachment may thus be a key factor in intergenerational transmission (IT) of CSA. Objective: The study aims to examine the direct, interactive, and mediated effects linking attachment in different relationships (mother, father, romantic partner) to IT of CSA among male victims. Participants and setting: Thirty-two abusing and 27 non-abusing male CSA survivors were recruited, respectively, in a prison and via networks of former foster children or CSA victims. Method: All participants completed the Attachment Multiple Model Interview to assess attachment along four dimensions (security, deactivation, hyperactivation, and disorganization) in the relationship with mother, father, and partner. Results: Partial least square modeling suggests that the partner carries forward (mediates) the increased risk of committing sexual abuse associated with insecure/disorganized attachment with the father. A significant partner-mother interaction also suggests that the deleterious effects of attachment to the mother in terms of committing CSA are countered by more secure/organized attachment to the partner. Conclusions: Findings highlight the pivotal role of the romantic partner in IT of CSA. Beyond early intervention, therapy in adulthood aimed at fostering adaptive ways of finding emotional security in the relationship with an adult could thus be encouraged.